2006
DOI: 10.1002/dmrr.650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia reoxygenation in brain slices from rats with type 1‐like diabetes mellitus

Abstract: The biochemical pathways involved in oxidative stress and neuronal death are more sensitive to hypoxia reoxygenation in type 1-like diabetic, as compared to normal, rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 103 publications
(95 reference statements)
2
11
0
Order By: Relevance
“…The four compounds showed cytoprotective effects separately in this experimental model, although HT and OLC showed greater potency than Ty and DHPG did. Using the same model, this effect has been previously described for HT [8,[15][16][17] and Ty [22,23] at the same proportions as in this study. OLC has demonstrated a neuroprotective effect on neuron-like SH-SY5Y cells induced with H 2 O 2 at proportions similar to those in our study and at similar concentrations [24].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The four compounds showed cytoprotective effects separately in this experimental model, although HT and OLC showed greater potency than Ty and DHPG did. Using the same model, this effect has been previously described for HT [8,[15][16][17] and Ty [22,23] at the same proportions as in this study. OLC has demonstrated a neuroprotective effect on neuron-like SH-SY5Y cells induced with H 2 O 2 at proportions similar to those in our study and at similar concentrations [24].…”
Section: Discussionmentioning
confidence: 58%
“…We chose the in vitro hypoxia-reoxygenation model using rat brain slices because it has been shown that, in this model, there is cell death accompanied by an increase in oxidative and nitrosative stress [ 16 , 17 ]. This was fulfilled in the present study, as can be seen in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Iadecola et al 30,31 reported that iNOS may be involved in neuronal death in the postischemic period because iNOS mRNA expression peaked at 24 hours after the ischemia in permanent ischemic brains and at 12 hours in transient ischemic brains after 2 hours of MCAO. 33,34 Overproduction of NO by nNOS and iNOS in the brain parenchyma has been demonstrated to contribute to tissue damage. 32 It was suggested that iNOS expression in the ischemic penumbra was associated with the recruitment of penumbra into infarction after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nervous tissue damage can occur in the peripheral nerves or in the central nervous system [4,5]. A greater sensitivity of the central nervous tissue to ischemic damage, independent of diabetic vascular alterations, was previously described in models of experimental diabetes [6,7]. Likewise, neuronal damage even earlier than vascular damage was described in the retinas of diabetic animals [8,9].…”
Section: Introductionmentioning
confidence: 99%